FEC Additive for Improved SEI Film and Electrochemical Performance of the Lithium Primary Battery - Xuan Zhou; Ping Li; Zhihao Tang; Jialu Liu; Shaowei Zhang; Yingke Zhou; Xiaohui Tian (Energies, 2021)
The solid electrolyte interphase (SEI) film plays a significant role in the capacity and storage performance of lithium primary batteries. The electrolyte additives are essential in controlling the morphology, composition and structure of the SEI film. Herein, fluoroethylene carbonate (FEC) is chosen as the additive, its effects on the lithium primary battery performance are investigated, and the relevant formation mechanism of SEI film is analyzed. By comparing the electrochemical performance of the Li/AlF3 primary batteries and the microstructure of the Li anode surface under different conditions, the evolution model of the SEI film is established. The FEC additive can decrease the electrolyte decomposition and protect the lithium metal anode effectively. When an optimal 5% FEC is added, the discharge specific capacity of the Li/AlF3 primary battery is 212.8 mAh g−1, and the discharge specific capacities are respectively 205.7 and 122.3 mAh g−1 after storage for 7 days at room temperature and 55 °C. Compared to primary electrolytes, the charge transfer resistance of the Li/AlF3 batteries with FEC additive decreases, indicating that FEC is a promising electrolyte additive to effectively improve the SEI film, increase discharge-specific capacities and promote charge transfer of the lithium primary batteries.